1997
DOI: 10.1266/ggs.72.91
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the recG gene product of Escherichia coli in recombination repair: Effects of the .DELTA.recG mutation on cell division and chromosome partition.

Abstract: The products of the recG and ruvAB genes of Escherichia coli are both thought to promote branch migration of Holliday recombination intermediates by their junction specific helicase activities in homologous recombination and recombination repair. To investigate the in vivo role of the recG gene, we examined the effects of a recG null mutation on cell division and chromosome partition. After UV irradiation at a low dose (5J/ m 2 ), ∆recG mutant formed filamentous cells with unpartitioned chromosomes. A mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
38
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 44 publications
9
38
0
Order By: Relevance
“…Genes to Cells (1998) 3, 209-220 217 (Cao & Kogoma 1995;Ishioka et al 1997). It should be noted that ⌬ruvAB and ⌬ruvC mutants showed identical phenotypes as to chromosome nonpartition, accumulation of nonmigrating DNA and UV sensitivity (data not shown), suggesting that all three Ruv proteins work co-operatively in resolving the Holliday junctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes to Cells (1998) 3, 209-220 217 (Cao & Kogoma 1995;Ishioka et al 1997). It should be noted that ⌬ruvAB and ⌬ruvC mutants showed identical phenotypes as to chromosome nonpartition, accumulation of nonmigrating DNA and UV sensitivity (data not shown), suggesting that all three Ruv proteins work co-operatively in resolving the Holliday junctions.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that a major in vivo role of RuvAB and RuvC proteins in repair of UV-induced lesion is the resolution of Holliday recombination intermediates, similar to the assigned role of these proteins in homologous recombination by in vitro studies. A recG mutant is also defective in chromosome partitioning but the defect is milder than for the ruv mutants (Ishioka et al 1997). Since RuvABC and RecG cannot substitute each other, they are not simple alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that a prfA mutant (recU::cat) is impaired in homologous recombination independently of other known rec genes (7). Since mutations in genes involved in homologous recombination are known to cause defects in chromosome segregation (15,36,50), it is possible that the chromosome segregation defect of prfA cells is due to a defect in homologous recombination. However, PrfA has no significant primary sequence homology to known recombinases, indicating that the effect of PrfA on homologous recombination may be indirect.…”
Section: Vol 182 2000mentioning
confidence: 99%
“…rad62-1 is synthetically lethal with mutations in the genes promoting recovery from stalled replication, such as rqh1, srs2, and mus81, and those involved in nucleotide excision repair like rad13 and rad16. These results suggest that Rad62, like Rad60, in conjunction with the Smc5-6 complex, plays an essential role in maintaining chromosome integrity and recovery from stalled replication by recombination.Mutants in Schizosaccharomyces pombe rad2, Saccharomyces cerevisiae RAD27, and Escherichia coli polA, all of which are defective in processing Okazaki fragments, are synthetically lethal with mutations in recombination repair genes (8,11,23,24,35,37,40,43,44). In these mutants, double strand breaks (DSBs) are thought to be produced when replication forks encounter the single strand gaps or nicks remaining unsealed due to the inefficient processing of Okazaki fragments, so they require a highly efficient capacity to repair DSBs for survival.…”
mentioning
confidence: 99%